2011
DOI: 10.1038/leu.2011.122
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of hypoxia, HIF-1 and HIF-2 in multiple myeloma

Abstract: Hypoxia is an imbalance between oxygen supply and demand, which deprives cells or tissues of sufficient oxygen. It is wellestablished that hypoxia triggers adaptive responses, which contribute to short-and long-term pathologies such as inflammation, cardiovascular disease and cancer. Induced by both microenvironmental hypoxia and genetic mutations, the elevated expression of the hypoxia-inducible transcription factor-1 (HIF-1) and HIF-2 is a key feature of many human cancers and has been shown to promote cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
118
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(127 citation statements)
references
References 146 publications
6
118
0
2
Order By: Relevance
“…28 Furthermore, a growing number of novel anticancer agents have been demonstrated to inhibit HIF-1a with different molecular mechanisms including histone deacetylases, molecules acting on RAS-RAK-MEK-ERK pathways and PI3K-AKT, and mTOR inhibitors, that are also currently in phase I-II clinical trials in MM. 1,29 Overall, our study provides the rationale for clinical trial with selective inhibitors of HIF-1a mRNA, such as EZN-2968 50 in MM patients.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…28 Furthermore, a growing number of novel anticancer agents have been demonstrated to inhibit HIF-1a with different molecular mechanisms including histone deacetylases, molecules acting on RAS-RAK-MEK-ERK pathways and PI3K-AKT, and mTOR inhibitors, that are also currently in phase I-II clinical trials in MM. 1,29 Overall, our study provides the rationale for clinical trial with selective inhibitors of HIF-1a mRNA, such as EZN-2968 50 in MM patients.…”
Section: Discussionmentioning
confidence: 88%
“…[16][17][18]22 HIF-1a is overexpressed in many tumors 22,23 including some hematological malignancies such as MM. [27][28][29]35 We and others 27,35 have recently shown that BM microenvironment is hypoxic both in MM patients 27 and in mice. 35 In addition HIF-1a also may be overexpressed by MM cells under normoxic conditions 27,28 dependent at least in part on c-myc upregulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIF is a heterodimeric complex composed of one α (eg, HIF‐1α or HIF‐2α) and one ÎČ‐subunit (HIF‐1ÎČ) 11. MM microenvironment is featured by hypoxia naturally existing in bone marrow niches where MM cells reside, which plays a critical role in MM cell survival, growth, metabolism, drug resistance, and angiogenesis, etc 13, 14, 15. To date, the studies of hypoxia in cancer (including MM) have focused almost exclusively on HIF‐1α, while the role of HIF‐1ÎČ remains a little known.…”
Section: Introductionmentioning
confidence: 99%
“…25 Under hypoxic conditions, cells express the transcription factor HIF-1a, which has been shown to sensitize cells to genotoxic stress. 26 We tested if HIF-1a expression could overcome genotoxic stress resistance in 8226 cells.…”
Section: Cell Cycle Arrest Can Be Overcome By Hif-1a Inductionmentioning
confidence: 99%